2010
DOI: 10.1161/circulationaha.109.931782
|View full text |Cite
|
Sign up to set email alerts
|

Adropin Is a Novel Regulator of Endothelial Function

Abstract: Background-Adropin is a recently identified protein that has been implicated in the maintenance of energy homeostasis and insulin resistance. Because vascular function and insulin sensitivity are closely related, we hypothesized that adropin may also exert direct effects on the endothelium. Methods and Results-In vitro cell culture models were partnered with an in vivo murine injury model to determine the potential vascular effects of adropin. Adropin was expressed in human umbilical vein and coronary artery e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
360
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(377 citation statements)
references
References 19 publications
12
360
0
5
Order By: Relevance
“…Activation of the ERK signaling pathway increases cell growth, and numerous extracellular stimuli regulates endothelial cell proliferation through manipulation of this pathway (9). Pre-treatment with PD98059 reduces endothelial cell proliferation induced by adiponectin, ghrelin and adropin (37)(38)(39). The present results confirmed the role of ERK signaling in mediating DHA-induced inhibition of endothelial cell proliferation.…”
Section: Discussionsupporting
confidence: 82%
“…Activation of the ERK signaling pathway increases cell growth, and numerous extracellular stimuli regulates endothelial cell proliferation through manipulation of this pathway (9). Pre-treatment with PD98059 reduces endothelial cell proliferation induced by adiponectin, ghrelin and adropin (37)(38)(39). The present results confirmed the role of ERK signaling in mediating DHA-induced inhibition of endothelial cell proliferation.…”
Section: Discussionsupporting
confidence: 82%
“…Adropin is encoded by the Energy Homeostasis Associated (Enho) gene that is widely expressed in the central nervous system, as well as peripheral tissues such as liver, the heart and skeletal muscles [14][15][16]. While the mechanism of release remains controversial, the rapid regulation according to energy and nutritional status has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Lovren et al [8] demonstrated that adropin could enhance the expression of endothelial nitric oxide synthase (eNOS) in the endothelium via activation of vascular endothelial growth factor receptor (EGFR) 2 phosphatidylinositol 3-kinase Akt and EGFR 2 extracellular signalregulated kinase 1/2 pathways. As eNOS is responsible for the production of vascular nitric oxide (NO) [13], adropin defi- Abbreviations: ACE = angiotensin-convertingenzym disease, CCB = calcium channel blocker, CCS = Can sure,SBP = systolic blood pressure and SVG = saphen me, ARB = angiotensin receptor block nadian Cardiovascular Society , CRP nous vein graft ker; BMI = body mass index, CAD = P = C-reactive protein, DBP = diastol = coronary artery olic blood presciency is associated with reduced nitric oxide bioavailability in the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Adropin appears to participate in the maintenance of energy homeostasis and insulin response, which is closely related to the development and progression of atherogenesis [7]. A recent study found that adropin is also expressed in coronary artery endothelial cells and plays a potential endothelial protective role in mice [8]. It is well known that endothelial dysfunction is a key early event in atherogenesis and is integral in the onset of CAD and acute coronary syndromes (ACS) [9].…”
mentioning
confidence: 99%